Priming and growth inhibitor in the production of high-quality pepper seedlings - Silva, Abimael Gomes [UNESP]; Silva Binotti, Flavio Ferreira da; Pinto Matos, Adriana Hernandes; Pereira da Silva, Talita Cristina Campos; Silva, Tatiane Carla [UNESP]; Costa, Edilson (Univ Estadual Mato Grosso Sul, 2021)
This study aimed to evaluate the effect of nitrate salts and a growth regulator on seed conditioning. Subsequently, the responses of the influence of the leaf application of paclobutrazol (PBZ) and nitrogen on the quality of seedlings of Capsicum frutescens L. were evaluated. Two experiments were carried out. The first experiment was conducted in a completely randomized design to evaluate priming, as follows: T1 - control, T2 - control (water), T3 - 0.2% calcium nitrate, T4 - 0.2% potassium nitrate, T5 - 0.1% calcium nitrate + 0.1% potassium nitrate, T6 - PBZ, and T7 - PBZ + 0.1% calcium nitrate + 0.1% potassium nitrate. The second experiment was carried out in a completely randomized design in a 2x5 factorial scheme consisting of priming (absence and presence of calcium nitrate) and leaf application of growth regulator, as follows: control (water), PBZ, PBZ + 1% nitrogen (calcium nitrate), PBZ + 1% nitrogen (urea), and PBZ + nitrogen (0.5% calcium nitrate + 0.5% urea). Physiological conditioning with a solution of 0.1% calcium nitrate increased the germination and seedling emergence rate and resulted in seedlings with a higher shoot length at 33 days after sowing (DAS), but seedlings at 50 DAS showed no differences in growth with its use. Leaf application of 0.1% paclobutrazol provided pepper (C. frutescens L.) seedlings with better distribution in growth according to the Dickson quality index.
Keywords: Capsicum frutescens L.; potassium nitrate; calcium nitrate; seedling quality